2019
DOI: 10.1038/s41598-019-48213-1
|View full text |Cite
|
Sign up to set email alerts
|

Co-carcinogenic effects of vitamin E in prostate

Abstract: A large number of basic researches and observational studies suggested the cancer preventive activity of vitamin E, but large-scale human intervention trials have yielded disappointing results and actually showed a higher incidence of prostate cancer although the mechanisms underlying the increased risk remain largely unknown. Here we show through in vitro and in vivo studies that vitamin E produces a marked inductive effect on carcinogen-bioactivating enzymes and a pro-oxidant status promoting both DNA damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
0
17
0
2
Order By: Relevance
“…Some still unsolved safety concerns should be considered as well. Vitamin E, in fact, has been suspected to have a dichotomous suppressive and promoting activity with respect to tumorigenesis [e.g., cocancerogenic in prostate cancer; (25,129)] possibly explainable by still poorly studied host gene-supplement interactions (130). In our opinion, further carefully designed studies are still necessary for substantiating this view and supporting optimum procedures in terms of both efficacy and safety profiles.…”
Section: Therapeutic Strategies Non-enzymatic Anti-oxidants Defensesmentioning
confidence: 94%
“…Some still unsolved safety concerns should be considered as well. Vitamin E, in fact, has been suspected to have a dichotomous suppressive and promoting activity with respect to tumorigenesis [e.g., cocancerogenic in prostate cancer; (25,129)] possibly explainable by still poorly studied host gene-supplement interactions (130). In our opinion, further carefully designed studies are still necessary for substantiating this view and supporting optimum procedures in terms of both efficacy and safety profiles.…”
Section: Therapeutic Strategies Non-enzymatic Anti-oxidants Defensesmentioning
confidence: 94%
“…The risk was increased by 17% at 7 years of median follow-up [ 40 ]. In vivo study indicated that vitamin E upregulated CYPs, including CYP1A1 and CYP1B1 which highly expressed in prostate cancer, increased ROS production and led to the mutation of prostate cells [ 41 ]. Therefore, males with prostate hyperplasia, elevated prostate-specific antigen or history of prostate cancer should be cautious when consuming high dose of vitamin E [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…This effect is probably due to the hepatic α‐TOH transfer protein, which preferentially incorporates α‐TOH into the plasma, as well as increasing hepatic catabolism of γ‐TOH to γ‐carboxyethyl‐hydroxychroman (γ‐CEHC) (γ‐TOH water‐soluble metabolite) (Devaraj, Leonard, Traber, & Jialal, ). Finally, it must be considered that α‐TOH, as synthetic isomer of vitamin E, has been reported to act as a co‐carcinogen in in vitro model systems (Vivarelli et al, ) in support of the hypothesis that α‐TOH might sustain prostate tumour growth (Klein et al, ).…”
Section: Discussionmentioning
confidence: 97%